Balancing Trade-offs between Deep Energy Retrofits and Heritage Conservation: A Methodology and Case Study. Issue 1 (2nd January 2022) - Ide, Larissa; Gutland, Michael; Bucking, Scott; Santana Quintero, Mario
ABSTRACT: Drastic reductions in energy consumption within existing buildings are required to achieve climate change mitigation targets. However, a portion of existing buildings have important historic values that need to be conserved. The goal of this paper is to present a methodology and decision-framework for deep energy retrofit analyses that balances trade-offs between conservation and sustainability. This methodology includes historic recording, documentation, a detailed energy model, and calibration to monthly data. An historic house in Ottawa, Canada is studied to demonstrate the use of the methodology. The energy retrofit analysis suggests 67% energy savings are achievable by increasing envelope thermal resistance to 4.1 m 2 -K/W, reducing air infiltration by 70% to 4.2 ACH at 50 Pa through air sealing and an air-vapour barrier, rehabilitating windows to be triple-pane low-E assemblies, using an air-source heat pump to supplement the existing gas boiler, daylight sensors and controls, and solar PV panels.